Health-related quality of life in acute myeloid leukemia patients not eligible for intensive chemotherapy: results of a systematic literature review - Forsythe A; Kwon CS; Bell T; Smith TA; Arondekar B (Dove Medical Press, 2019)
Anna Forsythe,1 Christina S Kwon,1 Timothy Bell,2 T Alexander Smith,3 Bhakti Arondekar4 1Purple Squirrel Economics, New York, NY, USA; 2Pfizer Inc, New York, NY, USA; 3Pfizer Ltd, Walton Oaks, UK; 4Pfizer Inc, Collegeville, PA, USA Background: AML is a rapidly progressing bone marrow cancer, with poor survival rates compared to other types of leukemia. IC and NIC as well as BSC treatment options are available; however, there is scant published literature on the impact of disease and treatment on the HRQoL in patients receiving NIC.Aim: This study determined the HRQoL among NIC AML patients.Materials and methods: Embase, Medline, Cochrane database, and conference abstracts were searched using the prespecified PICOS criteria from January 2000 to November 2017 for studies reporting HRQoL and patient preference utilities in NIC AML. Studies on patients with RAEB-t MDS, randomized clinical trials (RCTs), prospective observational studies, and patient surveys were included, while systematic reviews and meta-analyses were used for bibliographic searching.Results: Thirteen records from 12 original studies were identified. These included five records from four RCTs, three prospective studies, four patient survey studies, and one cost-effectiveness analysis. At baseline, NIC AML patients had poor HRQoL scores especially in fatigue (33) and GHS (50) on a 0–100 scale, with higher scores indicating better health. Low baseline HRQoL scores, especially PF and fatigue (<50) were shown to be significant independent predictors of poor survival. Clinical responders demonstrated meaningful improvements, especially in PF and fatigue, along with other health domains after being treated with NIC agents across several studies.Conclusion: HRQoL is poor for patients with NIC AML; measures such as fatigue and PF at baseline have been identified as independent prognostic factors for overall survival with several studies showing improvement in both domains with treatment. RCTs should incorporate evaluation of treatment impact on patients’ PF and fatigue as important measures of effectiveness. Keywords: acute myeloid leukemia, hematology, unfit, low intensity, hypomethylating agents, myelodysplastic syndrome